A comprehensive assessment of the age-friendly health system in Iran: gaps and recommendations - Badriyeh Karami; Maryam Tajvar; Abbas Ostadtaghizadeh; Mehdi Yaseri (BMC Geriatrics)
Abstract Background An age-friendly health system (AFHS) is essential to meet the health needs of older adults and improve their health status. This study was conducted to provide a comprehensive evaluation of the status of AFHS in Iran. Methods This assessment was conducted in 2023. Data collection was conducted using a self-made 52 items assessment tool. Three evaluators independently conducted the evaluation by various methods in parallel way including asking managers and informants within the health system (n = 20), observation, reviewing existing documents, and reviewing literature. Each item was scored from 0 to 10, and the overall score was calculated. Results The total score of the AFHS was 111.02 out of 520, which is approximately 21.35% of the total possible score. Among the domains of the AFHS, health governance, information, community involvement, and outcomes scored between 2 and 4 out of 10, with mean scores of 3.35, 2.16, 3.02, and 2.2, respectively. The other domains scored below 2. Conclusions The assessment result suggests that the evaluated indicators of the AFHS reveal deficiencies across all dimensions. Considering the diverse and complex health needs of the older adults, along with the observed challenges, it is imperative for policymakers and stakeholders to improve the situation by enacting suitable interventions.